Studi Pemodelan Respon Polarisasi Terinduksi dalam Kawasan Waktu (TDIP) terhadap Kandungan Mineral Logam, Sebuah Hasil Awal - Yatini Y; Djoko Santoso; Agus Laesanpura; Budi Sulistijo (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2017)
Modelling studies of Time Domain Induced Polarization (TDIP) performed to obtain the relationship between parameters responses to metallic mineral content. This study includes mathematical, forward, physical and inversion modelling. Mathematical modelling is done by solving the Laplace equation to obtain the IP responses. Forward modelling is done by developing a numerical workflow to generate theoretical curves. Physical modelling obtained the data from various parameters of target measurement. TDIP responses that compared with the theoretical curves are the results of mathematical modelling. The best response of IP can be obtained by inversion modelling. TDIP responses measurement by varying target’s metallic mineral content is done for understanding the relationship between them. The amplitude of IP responses in forward modelling is determined by target’s radius and depth ratio, and ratio of background resistivity and target’s resistivity. The higher target’s radius and depth ratio, the higher the amplitude. There is a good correlation between TDIP responses to the presence of the target and the possibility of metallic mineral content in target.